A survey of the YAN status of South African grape juices and exploration of multivariate data analysis techniques for spectrometric calibration and cultivar discrimination purposes. - Petrovic, Gabriella (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.